伊格言的科幻文学作品研究——以《噬梦人》、《零地点》和《零度分离》为例 = A study of Egoyan Zheng's science fiction novels: The Dream Devourer, GroundZero and Zero Degrees of Separation - 胡文瑄 Oh, Wen Xuan (Nanyang Technological University, 2025)
台湾科幻文学历经不同时代的发展而日趋成熟。随着时代的变化，台湾科幻作品所探讨的议题变得愈发深刻。本文将以伊格言目前所出版的科幻作品《噬梦人》、《零度分离》与《零地点》来分别对后人类世界中的身份、人在科技发展下的情感呈现以及人与环境的关系进行探讨，再深入探讨文本中的后人类主体性。文本试图解构后人类中心主义的狭隘观。在后人类的世界中，不同社会群体如生化人、女性以及人工智能的主体性探讨愈发强烈，同时反映出现实社会中存在的问题。 Science fiction literature in Taiwan has matured through the development of different eras. As time changes, the topic of discussion addressed in the Taiwanese science fiction works have deepened. This paper will be focusing on science fiction literature written by Egoyan Zheng, such as The Dream Devourer, Zero Degrees of Separation and GroundZero to address the topic of identity, emotions and environment in a technologically advanced posthuman society. These works attempt to deconstruct the anthropocentrism mindset. In the posthuman society, the discussion of subjectivity among different social group communities like cyborgs, women and artificial intelligence have increased, which also reflects relevant issues in the real-world context.